Snap-through behaviors of a pre-deformed ribbon under midpoint loadings. (1st December 2021) - Huang, Weicheng; Ma, Chao; Qin, Longhui
Abstract: Based on the geometrically nonlinear Kirchhoff rod theory, the snap-through behaviors of an asymmetrically clamped ribbon under midpoint loadings are explored through a numerical approach. The pre-compressed elastic ribbon would experience supercritical pitchfork bifurcation and transform into multiple stable/unstable patterns when subjected to lateral end translations. With its midpoint pushed through a prescribed path and beyond a threshold, the pre-deformed ribbon will jump to other inverted equilibrium configurations, which is known as snap-through buckling. Instead of the well-established snap-through behaviors in 2D bistable beams, we observe several different snap-through processes for the elastic ribbons in a 3D scenario. Exploiting the efficiency and robustness of our developed discrete model, a systematic parameter sweep is performed to quantify the snap-through processes of elastic ribbons in different boundary conditions and categories, and the results of which could provide a fundamental understanding of structural mechanics and further motivate the designs and applications of engineered systems.